Edukasi Pencegahan Masalah Menstruasi pada Remaja Melalui Kontrol Stres di Kabupaten Takalar - Fauziah Botutihe; Halimah, Nur; Selvi Selvi; Amanda Amanda; Citra Lestari; Alamsyah, Alamsyah (Jurnal Pengabdian Masyarakat, 2026)
Menstrual disorders among adolescent girls, including dysmenorrhea, irregular cycles, and premenstrual syndrome (PMS), represent a significant reproductive health challenge that is often worsened by psychosocial stress. Desa Ko’mara, Kabupaten Takalar, South Sulawesi, was selected as the program site due to the limited access of adolescent girls to reproductive health information and the absence of community-based education programs addressing the link between stress and menstrual health. This community service program aimed to improve knowledge and skills of adolescent girls in preventing menstrual problems through stress management strategies. The program employed an interactive health education approach, including informational presentations, group discussion, and hands-on demonstration of stress management techniques such as deep breathing, progressive muscle relaxation, and mindfulness. A total of 29 adolescent girls participated in the program. Evaluation was conducted using a pre-test and post-test questionnaire. Prior to the intervention, only 24.8% of participants possessed adequate knowledge on the topic. Following the educational session, this proportion increased to 75.2%, representing an improvement of 50.4 percentage points. These results indicate that structured, face-to-face health education with participatory methods is highly effective in enhancing reproductive health literacy among adolescent girls in underserved rural communities.